Sistem Pakar Diagnosa Penyakit Kura – Kura Air Dengan Metode Certainty Factor Berbasis Mobile - Zachary Osborn; Kartika Gunadi; Leo Willyanto Santoso (Jurnal Infra, 2021)
Turtle is on of the few animals that many people has interest in for pets,because turtles have this unique and beautiful shells. Turtle usually have a long age, butfor tortoise it is usually longer. In average tortoise can live up to 70 to 100 years. But stillall living things can get sick, including turtles. One of the actions that must be taken by water turtle keepers when their pet is sick is to know the symptoms and disease. Onealternative to find out what diseases our pets have is to go to the vet. But the price that veterinarians offer is relatively inexpensive.This expert system for diagnosis of water turtle disease is equipped with the Certainty Factor method. The usefulness of the Certainty factor method in this program is to display the level of system confidence in the diagnostic results in the form of a percentage. So that later serves to convince users when using this program.Based on the test results, this application can provide solutions that are suitable for diseases associated with symptoms. The results of the comparison between the Certainty Factor method and the Dempster Shafer method also give the same results in cases where the numbers used are the best numbers. The average figure resulting fromthis calculation is 83.6%.